ION EXCHANGE CHROMATOGRAPHY WITH CONDUCTIVITY DETECTION COMPARED TO SPECTROPHOTOMETRY TO ASSAY PHOSPHATE IN MILK AND MILK PRODUCTS - Tia Amina Setiawati; Fanny Guyomarc’h; Eric Beaucher; Frederic Gaucheron (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2015)
Phosphorus is a critical dietary mineral that is involved as phosphate in bone, tooth, nucleic acids or phospholipids and is mainly supplied through consumption of dairy products. Hence, it is important to be able to accurately and efficiently assay phosphate in dairy products. Currently, a colorimetric International Standard Organisation (ISO) reference method is used to assay phosphate in milk and cheese. This method requires large amounts of samples, of harmful chemicals and of manpower. In this paper, ionic exchange chromatography was used to assay phosphate on acid milk ultrafiltration permeate, milk, various cheeses and processed cheese and compared to the ISO method. The chromatographic method requires little amounts of materials and is automated. On the other hand, accuracy and precision were found to be less than those obtained with the reference method. In particular, phosphate was underestimated by the chromatographic method. Therefore, the chromatographic method is currently competitive for comparative assays, but not for absolute quantitation of phosphate. Research is still needed to fully upgrade the performances of this environment-friendly and time-saving method to those of the ISO reference.